2010
DOI: 10.1111/j.1523-5378.2010.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori Infection

Abstract: If we had to give a general view of the articles published in the year 2010, we should conclude that the evidence in the year 2010 suggests that, also in Helicobacter pylori diagnosis, "the devil is in the details". In this sense, different studies suggested that skipping citric acid pretreatment or local validation or reducing the (13) C-urea dose markedly decreases the accuracy of the urea breath test. The studies also implied that, even between monoclonal stool tests, there are large differences between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
0
24
1
2
Order By: Relevance
“…It has been proposed that PPI therapy lowers the sensitivity of UBT [39,40]; our data show, as it has been proved for invasive tests [41], that short courses of acid suppressive therapy, as we used while the patient was hospitalized, do not alter the performance of UBT. The presence of blood in the stomach, which is a limiting factor for invasive tests [34,42], does not seem to affect UBT accuracy either, as some authors say [43]. Unlike other studies [8], we did not find that age made any impact in UBT accuracy.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It has been proposed that PPI therapy lowers the sensitivity of UBT [39,40]; our data show, as it has been proved for invasive tests [41], that short courses of acid suppressive therapy, as we used while the patient was hospitalized, do not alter the performance of UBT. The presence of blood in the stomach, which is a limiting factor for invasive tests [34,42], does not seem to affect UBT accuracy either, as some authors say [43]. Unlike other studies [8], we did not find that age made any impact in UBT accuracy.…”
Section: Discussioncontrasting
confidence: 55%
“…We are aware of this limitation of our study, although other authors have found this unexpected falsepositive rate and low specificity [33]. Technical aspects in the procedure like pretreatment with citric acid should be improved in order to increase these suboptimal results [34]. Taking into account the mild severity of side-effects related to eradication therapy [35], it could be rational to perform early UBT at endoscopy and eradicate all positive patients, as empiric therapy in PUB is no longer recommended in developed countries [36] (although in countries with a very high prevalence of Hp, empiric therapy could be an option in terms of cost-effectiveness).…”
Section: Discussionmentioning
confidence: 86%
“…O teste ultrarrápido apresenta mais de 90% de sensibilidade (Calvet et al, 2010), mas pequenas alterações na coloração, mesmo positivas, podem não ser distinguidas do que é considerado normal (McIntosh et al, 2010).…”
Section: Resultsunclassified
“…The studies indicate that low socioeconomic status was one of the major risk factors for a high prevalence of H. pylori infection [16,23] . Eastern and Central European countries are in a transitional area, where the prevalence of H. pylori is not as low as in Western regions, but not as high as in the developing countries [27] .…”
Section: Referencesmentioning
confidence: 99%